The ELISA Guidebook - Crowther, J R (Humana Press, 2001)
Highly sensitive, precise, and versatile, Enzyme Linked Immunosorbent Assay (ELISA) is now the predominant assay used in biomedical and agricultural research, as well as in applied science. In The ELISA Guidebook, John R. Crowther provides todayís premier practical guide to the understanding and application of ELISA. Updating and greatly expanding his widely appreciated earlier publication, ELISA Theory and Practice (1995), this important work introduces such major new topics as checkerboard titrations, quality control of testing, kit production and control, novel monoclonal antibodies, validation of assays, statistical requirements for data examination, and epidemiological considerations. The author describes each method in great detail to ensure experimental success and includes advice on equipment choice, maintenance, and calibration. Wherever possible, helpful written explanations are provided along with copious diagrams. With its numerous worked examples, detailed instructions, and extensive illustrations, The ELISA Guidebook offers a powerful synthesis of all the basic concepts and practical experimental details investigators need to understand, develop, and apply the new ELISA methodology successfully in day-to-day basic and clinical research.